THE GENUS AESCHYNOMENE IN MALAYSIA (LEGUMINOSAE - PAPILIONATAE) - VELVA E. RUDD (Reinwardtia, 1959)
Seven species are found to occur in Malaysia,only Ae.aspera presumably being native there.Key,synonymy, descriptions,and particulars are given, besides indexes to collections and names.Some twenty or more species of Aeschynomene have been attributed to Malaysia, or "Ind. Or." When the specimens are examined,however, and the synonymy recognized, it appears that the number should be reduced to seven. One species, Ae. aspera, presumably is native to the area; Ae.elaphroxylon and Ae. uniflora are African species; Ae. americana, Ae. elegans, Ae. indica, and Ae. villosa are all believed to be natives of America.The writer is grateful to the curators of the following herbaria for making available the material for this study. The abbreviations of herbarium names used below and in the citation of specimens are those of Lanjouw and Stafleu (Index Herbariorum, 1, ed. 2. 1954).